Effect of Recruitment and Selection Practices on Employee Performance: An Empirical Study of East Wollega Zone Finance Office, Oromia, Ethiopia - Gudata Abara Chali; Lalisa Kenea Gamtessa (Journal of Organizational and Human Resource Development Strategies, 2026)
This study investigates the influence of recruitment and selection practices on employee performance within the East Wollega Zone Finance Office. In the modern public sector landscape, the acquisition of skilled human capital is recognized as a primary source of competitive advantage. Utilizing a mixed-methods approach with an explanatory research design, the study conducted a census survey of 63 permanent employees, yielding a 95.2% response rate. Data were analyzed using SPSS version 23 through descriptive statistics, Pearson correlation, and multiple linear regression. The empirical results reveal a strong positive correlation (r=0.564, p<0.01) between recruitment practices and performance. Regression analysis showed that the model explains 62.1% of the variance in employee performance (R2=0.621). Notably, the "Examination of HR Policies" emerged as the most significant predictor (B=0.438, p<0.001). Qualitative insights further indicated that while formal policies exist, there are gaps in transparency and feedback mechanisms. The study recommends that the zonal administration prioritize the modernization of recruitment criteria and institutionalize a merit-based selection framework to enhance public service delivery.